Female‐committed infanticide followed by juvenile‐enacted cannibalism in wild white‐faced capuchins - Kulick, Nelle (2021)
On 5 February 2021, we observed the frst instance of female-committed infanticide followed by cannibalism in a long- studied (>35 years) population of wild white-faced capuchins (Cebus imitator) in the Santa Rosa Sector of the Área de Conservación Guanacaste, Costa Rica. The events leading up to and including the infanticide and cannibalism were observed and documented ad libitum, with segments digitally recorded, and a post-mortem necropsy performed. Here we detail our observations and evaluate the events within the framework of leading adaptive explanations. The infanticide may have been proximately motivated by resource competition or group instability. The circumstances of the observed infanticide pro- vided support for the resource competition, adoption avoidance, and social status hypotheses of infanticide, but not for the exploitation hypothesis, as neither the perpetrator nor her kin consumed the deceased infant. The subsequent cannibalism was performed by juveniles who observed the infanticide and may have been stimulated by social facilitation and their prior experience of meat consumption as omnivores. To our knowledge, cannibalism has been documented only once before in C. imitator, in an adjacent study group, with the two cases sharing key similarities in the context of occurrence and manner of consumption. These observations add to our growing knowledge of the evolutionary signifcance of infanticide and its importance as a reproductive strategy in nonhuman primates.